Prolonged diarrhoea following acute gastroenteritis - Pitono Soeparto; Subijanto M. S.; Haroen Noerasid (Indonesian Pediatric Society, 1982)
Prolonged diarrhoea is defined as diarrhoea continuing for more than 7 days from the onset of effective regrading the feeds (slightly modified after Gribbin. 1976).84 infants treated ambulatory for prolonged diarrhoea were investigated for stool pathogens, fat malabsorption (Rossipal Melhod) and sugar malabsorptio (Clinitest Method).The clinical course of the illness was also studied.The diarrhoea lasted in most of the cases between 10- 25 days. Over three quarters of the infants were aged less than 1 year.53.6% of Ihe infants excreted intestinal pathogen: path. E. coli (31%), Salmonella Sp. (17.9%), Staphylococcus aureus (10.7.%), and E. Coli aggl. neg.(1.2%).Lactse intolerance and gross fat malabsorption accounted resp. for 5% and 41.7% of infants with prolonged diarrhea.Â